Orthopedic surgeons’ views on the osteoporosis care gap and potential solutions: survey results - David W. Barton; Daniel C. Griffin; Jonathan J. Carmouche (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Introduction Osteoporosis is often not recognized until one or more fractures occur, yet post-fracture screening remains uncommon. Orthopedic surgeons are well situated to address this care gap. Both a protocol-based approach and fracture liaison services (FLS) have been proposed. The present surveys assess orthopedists’ attitudes to these alternative models for addressing this care gap. Methods Two digital surveys were sent to all orthopedic surgeons and orthopedic midlevel providers at a large level 1 trauma center 1.5 years apart. Results Thirty-six of 47 survey recipients (77%) responded to the first survey; all 55 recipients (100%) responded to the second. Respondents recognized the importance of osteoporosis care, the inadequacy of current measures, and the potential of orthopedic surgeons to help address this gap. Respondents reported regular encounters with fragility fracture patients but limited familiarity with core aspects of osteoporosis screening and treatment, especially pharmacotherapy. While some respondents (40%) reported willingness to attempt a protocol-based approach to addressing this care gap, many others expressed reservations (60%) and support for a FLS-based approach was much higher (95%). Conclusions A fracture liaison service model best fits the observed attitudes of orthopedic surgeons at this level 1 trauma center relative to a protocol-based approach. Protocol-based approaches may be preferable in alternate settings.